12 Genetic analysis of primary and recurrent adult granulosa cell tumors of the ovary. (18th September 2019) - Da Cruz Paula, A; da Silva, E; Segura, S; Bi, R; Selenica, P; Pareja, F; Vidal, A; Gatius, S; Abu-Rustum, NR; Matias-Guiu, X; Rubin, BP; Reis-Filho, J; et al.
Abstract : Objectives: Adult granulosa cell tumors (aGCTs) are rare ovarian tumors underpinned by the FOXL2 p.C134W mutation, with a 10–30% risk of relapse. We sought to determine the genetic alterations underpinning primary and recurrent aGCTs. Methods: Thirty-five aGCTs were subjected to massively parallel sequencing targeting 468 cancer-related genes (7 primary aGCTs that did not recur >4 years, 9 primary and matched recurrent aGCTs, 10 recurrent aGCTs). These cases and additional 12 aGCTs (n=3, primary aGCTs that did not recur; n=9, recurrent aGCTs) were subjected to Sanger sequencing analysis of the TERT promoter. Results: All aGCTs included harbored the FOXL2 p.C134W hotspot mutation. A significantly higher frequency of TERT promoter mutations was found in recurrent (64%) than in primary aGCTs (26%; p =0.017). Moreover, aGCT recurrences harbored a higher frequency of somatic KMT2D and TP53 mutations (16%, each) than primary aGCTs with subsequent recurrences (11% and 0%) and primary aGCTs without subsequent recurrences (14% and 0%). We identified a higher frequency of CDKN2A/B homozygous deletions in recurrent (16%) than in primary aGCTs (6%), and other gene alterations restricted to recurrent aGCTs. Pathway analysis revealed that aGCTs are underpinned by genetic alterations affecting the cell cycle pathway. Clonal decomposition of matched primary and recurrent aGCTs showed that aGCTs display multiple clones at diagnosis and relapse. Conclusions: Our findings suggest that although FOXL2 plays a crucial role in the tumorigenesis of aGCTs, recurrences might be associated with genetic alterations affecting TERT, cell cycle-related genes such as TP53 and CDKN2A/B, and other cancer-related genes, including KMT2D, TET2 and EPHA5 .